UKURAN PEMERINTAH, KUALITAS INSTITUSI, DAN PERTUMBUHAN EKONOMI REGIONAL DI INDONESIA (Jurnal Kebijakan Ekonomi, 2021)
The implementation of fiscal decentralization has brought significant changes to the management of public finances in Indonesia. Decentralization has been empirically proven to increase the size of government (ratio of government spending to output). Good institutional quality is considered as an important factor to ensure government spending is effective and able to contribute positively to the economy. This study aims to determine whether the influence of government size on economic growth depends on the quality of the institution. The study uses the level of analysis in 491 districts / municipalities in Indonesia during 2011-2017. Using Ordinary Least Square (OLS) estimation method, empirical results show that government size has a negative and significant effect on regional economic growth. By using an indicator of institutional quality, namely the democracy index, the empirical results of this study show the difference in the effect of government size depending on the quality of the institution. The negative effect of government size tends to be greater in regions with low institutional quality. Keywords: government size; quality of institutions; economic growth